Rapid activation of diazirine biomaterials with the blue light photocatalyst - Djordjevic, Ivan (2021)
Carbene-based macromolecules are an emerging new stimuli-sensitive class of biomaterials that avoid the impediments of free radical polymerization but maintain a rapid liquid-to-biorubber transition. Activation of diazirine-grafted polycaprolactone polyol (CaproGlu) is limited to UVA wavelengths that have tissue exposure constraints and limited light intensities. For the first time, UVA is circumvented with visible light-emitting diodes at 445 nm (blue) to rapidly activate diazirine-to-carbene covalent cross-linking. Iridium photocatalysts serve to initiate diazirine, despite having little to no absorption at 445 nm. CaproGlu's liquid organic matrix dissolves the photocatalyst with no solvents required, creating a light transparent matrix. Considerable differences in cross-linking chemistry are observed in UVA vs visible/photocatalyst formulations. Empirical analysis and theoretical calculations reveal a more efficient conversion of diazirine directly to carbene with no diazoalkane intermediate detected. Photorheometry results demonstrate a correlation between shear moduli, joules light dose, and the lower limits of photocatalyst concentration required for the liquid-to-biorubber transition. Adhesion strength on ex vivo hydrated tissues exceeds that of cyanoacrylates, with a fixation strength of up to 20 kg·f·cm2. Preliminary toxicity assessment on leachates and materials directly in contact with mammalian fibroblast cells displays no signs of fibroblast cytotoxicity.